Community Gardens i USA : en studie av rörelsens uppkomst, funktioner och effekter samt en jämförelse med liknande fenomen i Sverige - Melin, Emelie (SLU/Landscape Architecture (until 121231), 2010)
This paper originates in a study of Community Gardens in the United States. An overview of how and why the gardens have emerged, their functions today, and their effects and problems is presented. The reader will also be introduced to a selection of Swedish movements that correspond with the phenomenon of the American Community Garden. These are as follows; The Allotment Garden, the Swedish term Stadsdelsträdgård (a metaphor for a Community Garden in a Swedish urban context), Mykorrhiza Malmö Stadsodlare and The Allotment Plot. None of the above-mentioned Swedish movements can be described as an exact equivalent of the American Community Garden, but they all contain elements witch constitutes parts of the phenomenon. The traditional Swedish Allotment Garden is the phenomenon that shares the historical context in which the Community Garden developed, while the term Stadsdelsträdgård can be seen as the link that connects Sweden to Community Gardens in the future. Mykorrhiza Malmö Stadsodlare, is a movement which with permission from the municipality (and sometimes without) creates urban cultivations on city-owned, or other vacant, pieces of land (Mykorrhiza 2010 [online]). Mykorrhiza is one of the new movements that have emerged in Sweden in this context. Demonstrating an experimental and openminded attitude toward the use of public space, their methods are in some ways similar to those used in the occupation of public places in the United States. Initiatives of this kind have previously been unusual in the Swedish approach to common space, and the concept contains potential to overcome mental limits, considering the use of place in the Swedish context. The Allotment Plot is a network which works on a conceptual level, raising questions of sustainability through the process of involving people in a do-it-your-self-cultivation project. To ally yourself with the movement you pick up a box, fill it with soil, and start cultivating somewhere close to your home (The Allotment Plot 2010, [online]). Through the website, the movement reaches out and contributes with the idea of an "unsecured" design process (Söderberg 2009), where the Landscape architect and Planner strives towards reduced control in the process of designing public spaces and thereby invites the user to become the designer of the environment in which she is to thrive. The purpose of this essay was to study how the Community Garden movement functions today and which effects that are generated by its operations. By comparing the results to the structure and outcomes of the Swedish examples above, the ambition was to be able to discern whether a development towards Community Gardens like the ones found in the U.S. would be desirable in Sweden. Considering the substantial amount of positive effects that was identified, including increased safety, a richer social life in the neighbourhoods and economical gains, it was concluded that a development of Community Gardening indeed would be desirable in Sweden. Therefore, the longterm objective that will begin after the completion of this essay, is to examine whether such a development is possible in Sweden today. Could Community Gardens in that case become a tool which helps us contribute to healthier and more attractive dwellings for all the people of Sweden, and, as that, become an integral part of the planning process? ************** Denna uppsats tar avstamp i en undersökning av Community Gardens i USA. En översikt över varför trädgårdarna har uppstått, deras funktioner, effekter och problematik studeras. Det kommer även att läggas fram material om några av de motsvarigheter till begreppet Community Garden som vi kan spåra i Sverige; kolonilotten, (det ännu så länge metaforiska) begreppet Stadsdelsträdgård, Mykorrhiza Malmö Stadsodlare och The Allotment Plot. Ingen av de ovan nämnda svenska rörelserna kan sägas vara en direkt motsvarighet till en amerikansk Community Garden men alla bär de på element som återfinns i fenomenet. Kolonilotten är den företeelse som delar den historiska kontext i vilken Community Gardens uppstått, medan Stadsdelsträdgården kan ses som en faktor som kopplar Sverige till Community Gardens i framtiden. Föreningen Mykorrhiza Malmös intressecirkel Stadsodlare, som i samförstånd med kommunen (och ibland även utan) skapar sina egna gemensamma odlingsytor i staden (Mykorrhiza 2010 [online]), är en av de nya rörelser som uppstått i Sverige som visar på ett experimentellt och öppet förhållningssätt till det offentliga rummet. I deras handlingsmönster kan man dra paralleller till besittningstagandet av allmänna platser i USA. Liknande initiativ har det tidigare varit brist på i den svenska brukartraditionen och fenomenet visar på möjligheter att överbrygga mentala gränser för användande av en plats. The Allotment Plot, arbetar som ett nätverk där begrepp som hållbarhet och ekologi diskuteras genom ett koncept där brukaren uppmanas att alliera sig med rörelsen och odla på en yta nära sin bostad (The Allotment Plot 2010, [online]). Via hemsidan sprider rörelsen sig vidare ut i världen och för med sig en tanke om en ”osäkrad” designprocess (Söderberg 2009), där landskapsarkitekt och planerare strävar mot en minskad kontroll över platsen och därmed ett större överlämnande av ansvar för gestaltandet av det offentliga rummet till brukaren. Syftet med denna uppsats var att genom studier av det Amerikanska fenomenet Community Gardens kartlägga hur rörelsen fungerar idag samt vilka effekter som kunde utläsas i dess spår. Genom att jämföra resultatet med motsvarade struktur och utkomster från ovan nämnda svenska exempel, var förhoppningen att kunna utröna om en utveckling av gemensamma trädgårdar lik den i USA skulle vara önskvärd i Sverige. Mot bakgrund av de resultat som framkom, där bl.a. ökad gemenskap, tryggare boendemiljöer och ekonomiska vinster både för boende och markägare påvisades, kunde det styrkas att en sådan utveckling vore väl värd att främja i Sverige. Därför, blir det långsiktiga målet som tar vid efter denna uppsats färdigställande, att undersöka om en sådan utveckling är möjlig i Sverige idag. Kan Community Gardens i så fall bli ett verktyg i arbetet för att skapa tryggare, hälsosammare och vackrare boendemiljöer för alla, även de mindre bemedlade i Sverige, och, en självklar del av planeringsprocessen?